ECTODERMAL DYSPLASIA: CLINICAL AND THERAPEUTIC ASPECTS IN A LITERATURE REVIEW (CIPEEX, 2025)
Ectodermal dysplasia (ED) comprises a rare and heterogeneous group of genetic conditions, characterized by alterations in the development of at least two ectoderm-derived structures, namely: dentition, hair, nails, and sweat glands. The present study aims to conduct a literature review on the subject, highlighting its clinical aspects and the relevance of a multidisciplinary approach in patient management. Articles were searched in the PubMed, SciELO, and Google Scholar databases, which provided the basis to emphasize the need for dental practice to be integrated into multidisciplinary treatment. Ectodermal dysplasia represents a complex genetic disorder whose management requires an integrated approach from professionals such as dermatologists, endocrinologists, and psychologists, among others. Although there is no curative treatment for ED, dentists must be able to recognize the characteristic signs of the syndrome, facilitating early diagnosis. Once confirmed, it is essential that the patient be monitored by a multiprofessional team to ensure functional, emotional, and quality of life improvements. Therefore, dentistry plays a central role in developing individualized oral rehabilitation strategies for each stage of development, contributing to the restoration of self-esteem and the social inclusion of affected individuals.
Keywords: Ectodermal Dysplasia; Multiprofessional Approach; Oral Rehabilitation